Specialization And Adjustment During The Growth of China And India : The Latin American Experience - Lederman, Daniel 1968- (The World Bank, 2007)
This paper examines the extent to which the growth of China and India in world markets is affecting the patterns of trade specialization in Latin American economies. The authors construct Vollrath's measure of revealed comparative advantage by 3-digit ISIC sector, country, and year. This measure accounts for both imports and exports. The empirical analyses explore the correlation between the revealed comparative advantage of Latin America and the two Asian economies. Econometric estimates suggest that the specialization pattern of Latin A-with the exception of Mexico-has been moving in opposite direction of the trade specialization pattern of China and India. Labor-intensive sectors (both unskilled and skilled) probably have been negatively affected by the growing presence of China and India in world markets, while natural resource and scientific knowledge intensive sectors have probably benefited from China and India's growth since 1990